1997
DOI: 10.1164/ajrccm.155.4.9105072
|View full text |Cite
|
Sign up to set email alerts
|

Bovine surfactant therapy for patients with acute respiratory distress syndrome.

Abstract: Lung surfactant is deficient in patients with acute respiratory distress syndrome (ARDS). We performed a randomized, prospective, controlled, open-label clinical study of administration of a bovine surfactant to patients with ARDS to obtain preliminary information about its safety and efficacy. Patients received either surfactant by endotracheal instillation in addition to standard therapy or standard therapy only. Three different groups of patients receiving surfactant were studied: patients receiving up to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
171
0
13

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(189 citation statements)
references
References 20 publications
5
171
0
13
Order By: Relevance
“…However, interpretation of these negative results is confounded because both laboratory and clinical studies have documented that Exosurf® has low activity compared to animal-derived surfactants [51, [113][114][115][116][117][142][143][144][145], and aerosolization has not been shown to be as effective as airway instillation in delivering surfactant. Gregory et al [137] reported small benefits in oxygenation in a controlled trial in adults with ARDS who received four 100 mg/kg doses of Survanta®, but with no overall advantage in survival in the 43 surfactant-treated patients studied. A more recent study by Spragg et al [26] using recombinant SP-C surfactant (Venticute®) in adults with ARDS showed immediate improvements in oxygenation, but no longer-term improvement in duration of mechanical ventilation, lengths of stay, or mortality.…”
Section: Current Studies On Surfactant Replacement Therapy In Patmentioning
confidence: 99%
See 2 more Smart Citations
“…However, interpretation of these negative results is confounded because both laboratory and clinical studies have documented that Exosurf® has low activity compared to animal-derived surfactants [51, [113][114][115][116][117][142][143][144][145], and aerosolization has not been shown to be as effective as airway instillation in delivering surfactant. Gregory et al [137] reported small benefits in oxygenation in a controlled trial in adults with ARDS who received four 100 mg/kg doses of Survanta®, but with no overall advantage in survival in the 43 surfactant-treated patients studied. A more recent study by Spragg et al [26] using recombinant SP-C surfactant (Venticute®) in adults with ARDS showed immediate improvements in oxygenation, but no longer-term improvement in duration of mechanical ventilation, lengths of stay, or mortality.…”
Section: Current Studies On Surfactant Replacement Therapy In Patmentioning
confidence: 99%
“…However, many of these are small case series or pilot studies, and found only improvements in acute lung function (oxygenation). Controlled trials of surfactant therapy in patients with ALI/ARDS have met with mixed success, particularly in adults with sepsis-associated ARDS [136,137]. A summary of the clinical experience with exogenous surfactant therapy in term infants, children and adults is given below.…”
Section: Current Studies On Surfactant Replacement Therapy In Patmentioning
confidence: 99%
See 1 more Smart Citation
“…Instillation of surfactant into sepsis-induced ARDS patients improved gas exchange and mortality rate only in the group receiving four doses of 100 mg/kg compared with other groups receiving eight doses of 50 mg/kg or 100 mg/kg, respectively [8], suggesting that the benefits of subsequent dosing regimens are random. Spragg et al [9] evaluated the anti-inflammatory effects of SP-C-based surfactant in patients with ARDS.…”
Section: Discussionmentioning
confidence: 95%
“…In turn, injury predisposes the patient to acute (or adult) respiratory distress syndrome (ARDS) (1)(2)(3)(4). Pulmonary surfactant replacement, now a mainstay in the treatment of respiratory distress syndrome in premature infants, has not enjoyed comparable success in treating ARDS (5)(6)(7). Inadequate dosage or distribution, and inactivation of surfactant have been postulated for its poor performance in treating these injuries (8 -11).…”
mentioning
confidence: 99%